PENGARUH PELATIHAN TERHADAP KINERJA PETUGAS PEMADAM KEBAKARAN PADA DINAS SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN KEPULAUAN MENTAWAI - F Yasmeardi; Rini Parmila Yanti; Pathul Arifin (Jurnal Public Administration, Business and Rural Develoment Planning, 2020)
From the results of the study the following conclusions are made: 1. Training of Damkar officers for the field because the area of Mentawai Islands is quite extensive and also the problem of budget for field operations including the lack of fire trucks. 2. Firefighters in the field are quite good because officers already know what needs to be done both individually and as a team, but to improve the performance of fire fighters certainly need professional training specifically training damkar. 3. Based on the hypothesis test (t test), the value of tcount is 8,051 while ttable is 2,000. Thus tcount 8,051> ttable 2,000, so that (Ho) is rejected and (Ha) is accepted, it means that there is an influence between Training on Performance. The Determinant Coefficient (R-Square) The Effect of Training (X) is 0.495 or 49.5%. Thus variations in the increase and decrease in Performance (Y) can be explained by the Training variable by 49.5%, while the remaining 50.5% Performance is influenced by other factors not included in the variables studied. Through the regression test Y = a + bX obtained Y = 10,432 + 0.515 (Training), this shows the positive influence generated by the Training on Performance. This means that if Training (X) is increased by 1 point it will have an effect on the Performance of 10.9432 + 0.515. From the conclusions above, it can be suggested as follows: 1. Need to Increase Training of Damkar Officers in the field because there are still many officers who have not participated in the training besides that the budget is still limited 2. The leadership must increase the Damkar operational budget and also the training fund of Damkar officers.